Skip to main content
$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

# Section 6.2 Answers

$$\newcommand{\vecs}[1]{\overset { \scriptstyle \rightharpoonup} {\mathbf{#1}} }$$ $$\newcommand{\vecd}[1]{\overset{-\!-\!\rightharpoonup}{\vphantom{a}\smash {#1}}}$$$$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\id}{\mathrm{id}}$$ $$\newcommand{\Span}{\mathrm{span}}$$ $$\newcommand{\kernel}{\mathrm{null}\,}$$ $$\newcommand{\range}{\mathrm{range}\,}$$ $$\newcommand{\RealPart}{\mathrm{Re}}$$ $$\newcommand{\ImaginaryPart}{\mathrm{Im}}$$ $$\newcommand{\Argument}{\mathrm{Arg}}$$ $$\newcommand{\norm}[1]{\| #1 \|}$$ $$\newcommand{\inner}[2]{\langle #1, #2 \rangle}$$ $$\newcommand{\Span}{\mathrm{span}}$$

1. $$y=\frac{e^{-2t}}{2}(3\cos 2t-\sin 2t)\text{ ft};\:\sqrt{\frac{5}{2}}e^{-2t}\text{ ft}$$

2. $$y=-e^{-t}\left(3\cos 3t+\frac{1}{3}\sin 3t \right)\text{ ft}\frac{\sqrt{82}}{3}e^{-t}\text{ ft}$$

3. $$y=e^{-16t}\left(\frac{1}{4}+10t \right)\text{ ft}$$

4. $$y=-\frac{e^{-3t}}{4}(5\cos t+63\sin t)\text{ ft}$$

5. $$0\leq c<8\text{ lb-sec/ft}$$

6. $$y=\frac{1}{2}e^{-3t}\left(\cos\sqrt{91}t+\frac{11}{\sqrt{91}}\sin\sqrt{91}t \right)\text{ ft}$$

7. $$y=-\frac{e^{-4t}}{3}(2+8t)\text{ ft}$$

8. $$y=e^{-10t}\left(9\cos 4\sqrt{6}t+\frac{45}{2\sqrt{6}}\sin 4\sqrt{6}t \right)\text{ cm}$$

9. $$y=e^{-3t/2}\left(\frac{3}{2}\cos\frac{\sqrt{41}}{2}t+\frac{9}{2\sqrt{41}}\sin\frac{\sqrt{41}}{2}t \right)\text{ ft}$$

10. $$y=e^{-\frac{3}{2}t}\left(\frac{1}{2}\cos\frac{\sqrt{119}}{2}t-\frac{9}{2\sqrt{119}}\sin\frac{\sqrt{119}}{2}t \right)\text{ ft}$$

11. $$y=e^{-8t}\left(\frac{1}{4}\cos 8\sqrt{2}t-\frac{1}{4\sqrt{2}}\sin 8\sqrt{2}t \right)\text{ ft}$$

12. $$y=e^{-t}\left(-\frac{1}{3}\cos 3\sqrt{11}t+\frac{14}{9\sqrt{11}}\sin 3\sqrt{11}t \right)\text{ ft}$$

13. $$y_{p}=\frac{22}{61}\cos 2t+\frac{2}{61}\sin 2t\text{ ft}$$

14. $$y=-\frac{2}{3}(e^{-8t}-2e^{-4t})$$

15. $$y=e^{-2t}\left(\frac{1}{10}\cos 4t-\frac{1}{5}\sin 4t \right)\text{ m}$$

16. $$y=e^{-3t}(10\cos t-70\sin t)\text{ cm}$$

17. $$y_{p}=-\frac{2}{15}\cos 3t \frac{1}{15}\sin 3t\text{ ft}$$

18. $$y_{p}=\frac{11}{100}\cos 4t+\frac{27}{100}\sin 4t\text{ cm}$$

19. $$y_{p}=\frac{42}{73}\cos t+\frac{39}{73}\sin t\text{ ft}$$

20. $$y=-\frac{1}{2}\cos 2t+\frac{1}{4}\sin 2t\text{ m}$$

21. $$y_{p}=\frac{1}{c\omega _{0}}(-\beta\cos\omega _{0}t+\alpha\sin\omega _{0}t)$$

24. $$y=e^{-ct/2m}\left(y_{0}\cos\omega_{1}t+\frac{1}{\omega _{1}}(v_{0}+\frac{cy_{0}}{2m})\sin\omega _{1}t \right)$$

25. $$y=\frac{r_{2}y_{0}-v_{0}}{r_{2}-r_{1}}e^{r_{1}t}+\frac{v_{0}-r_{1}y_{0}}{r_{2}-r_{1}}e^{r_{2}t}$$

26. $$y=e^{r_{1}t}(y_{0}+(v_{0}-r_{1}y_{0})t)$$